Attitudes Toward Advanced Licensing for Macro Social Work Practice. Issue 1 (2nd January 2016) - Plitt Donaldson, Linda; Fogel, Sondra J.; Hill, Katharine; Erickson, Christina; Ferguson, Sarah
ABSTRACT: Trends in clinical licensing and a renewed energy to strengthen macro practice are raising questions about the appropriateness of licensure for macro social work practice. This article presents findings from an online survey of macro social work educators and macro social work practitioners exploring their attitudes toward an advanced-level macro social work license. Faculty and practitioner responders agreed that there is a role for advanced-licensing of macro social work practice; however, the lack of a collectively strong response reflects a current state of ambivalence toward advanced-level licensing for macro practice. Implications from these findings on contemporary social work are discussed.